Prevalence and determinants of anemia among pregnant women attending maternal and child health clinics at Sukuta Health Center, The Gambia: An institutional-based cross-sectional study - Fatou Mbowe; Kalifa Sanneh Darboe; Abdoulie M. Sanyang; Amadou Barrow (Women's Health)
Background: Anemia during pregnancy remains a significant global health concern, particularly in developing countries, contributing to adverse maternal and fetal outcomes. In The Gambia, despite national health policies promoting iron supplementation and malaria prevention, maternal anemia continues to be a common cause of morbidity and mortality. This study aimed to determine the prevalence and determinants of anemia among pregnant women attending maternal and child health clinics at Sukuta Health Center in The Gambia. Methods: An analytical institutional-based cross-sectional study was conducted on 425 pregnant women attending antenatal care. Data were collected using a structured questionnaire covering sociodemographic characteristics, knowledge of anemia, and anemia prevention practices. Hemoglobin levels were measured to determine the anemia status. Chi-square tests and a binary logistic regression model were used to assess the associations between variables, with statistical significance set at p  < 0.05, adjusted odds ratio (aOR) with 95% confidence intervals (CI). Results: The prevalence of anemia among pregnant women was 21.6%. The majority of women (55.3%) demonstrated good knowledge of anemia during pregnancy. The husbands’ occupational status was significantly associated with anemia ( p  = 0.036). Recognition of anemia symptoms was strongly associated with anemia status ( p  < 0.001). While 88.7% of the women recognized the importance of a nutritious diet in preventing anemia, only 46.9% mentioned iron supplements as a preventive measure. Nurses were the primary source of information about anemia (97.2%). Pregnant women who were Muslim had 4.3 times higher odds of being anemic (aOR = 4.295, 95% CI: 1.103–16.727) than those who were Christian after controlling for confounders. Conclusion: Despite the lower prevalence of anemia, there remains a need for improved comprehensive understanding and prevention practices. The significant association between husbands’ occupation and anemia status highlights the importance of considering household economic factors in anemia prevention. There is a need to design culturally tailored interventions targeting larger, resource-constrained Muslim households to effectively address anemia during pregnancy.